Creative Marketing in Media - Aleksandra Brakus (In Medias Res, 2016)
Art is a human activity which aims to stimulate the senses, mind and spirit. It is an activity that was created with the intention to transmit emotions and ideas. The need for art comes from human creativity. Many scientific disciplines such as psychology, sociology, art, are exploring the concept of creativity. The presence of creativity in marketing is not sufficiently explored. We live in a time that is characterized by rapid technological advances and changes. We are meeting with a large number of advertisements and our consciousness has already built a “defense” against advertising. We do not notice many advertisements and become blind to most of them. Companies must be extremely creative if they want to send a specific message and to gain public attention. Creative marketing is a combination of marketing and creativity. It is useful in theoretical and practical terms, and can use all types of media to achieve their goal. Creativity has benefits of marketing because it can express through it, and the marketing gets benefits of creativity because on that way it gets a new look and a becomes a marketing of new age.